2016
DOI: 10.1080/13691457.2016.1256869
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the interests of birth mother and child: a qualitative study of Swedish social workers’ experiences of transnational gestational surrogacy

Abstract: Gauging the interests of birth mother and child: a qualitative study of Swedish social workers' experiences of transnational gestational surrogacy Avvägningar mellan den biologiska moderns och barnets intressen: En kvalitativ studie av svenska familjerättsekreterares erfarenheter av transnationellt surrogatmoderskap ABSTRACTThere are few studies on how social workers deal with cases regarding transnational surrogacy. Our study intends to contribute to filling this gap. In Sweden, surrogacy as an assisted repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The consequences of unclear laws have made Swedish social service officials – those who deal with the issues around legal parenthood after surrogacy arrangements – struggle with concerns about the surrogate mother while simultaneously trying to secure the legal situation for the child ( Arvidsson et al, 2016 ). The issue for these officials was whether the surrogate mother had consented to the relinquishing of the child, which they were not able to establish as no direct contact was made with her.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of unclear laws have made Swedish social service officials – those who deal with the issues around legal parenthood after surrogacy arrangements – struggle with concerns about the surrogate mother while simultaneously trying to secure the legal situation for the child ( Arvidsson et al, 2016 ). The issue for these officials was whether the surrogate mother had consented to the relinquishing of the child, which they were not able to establish as no direct contact was made with her.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study among social service officials in Sweden indicated great disparities and uncertainty in the practice of legal parenthood decisions after surrogacy arrangements have been made ( Arvidsson et al, 2016 ). The aim of the present study was to investigate how Swedish commissioning parents have experienced the process of seeking official parenthood status when using transnational surrogacy.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that they need more knowledge about surrogacy and the health of the surrogate mother, the child and family, as well as guidelines on how to care for the family group. Similarly, a study among Swedish social workers showed that the lack of clear guidelines about what laws were applicable when they were contacted by commissioning parents who wanted to become the legal parents of a surrogate child led them to handling the cases in different ways and with great uncertainty. These findings, combined with the discrepancies between beliefs about the child's health and previous research findings, highlight the need for educational interventions for healthcare professionals working in child health care, as well as the development of adequate guidelines on surrogacy.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Sweden (the only one we were able to identify in this context) reinforces this assumption. Arvidsson et al (2018) found that, while Sweden bans surrogacy, its social workers are nevertheless faced with Swedish intended parents' applications to legalize the status of children born through transnational surrogacy. In many cases, these social workers give up their moral beliefs against surrogacy, put aside their concerns regarding the foreign surrogates' interests and rights, and recommend the children be granted full legal status by the court.…”
Section: Regulating Transnational Surrogacy Via the Legal System Of Tmentioning
confidence: 99%